A comparative study of the 2013 typhoon Haiyan overwash sediments from a coastal cave and beach system at Salcedo, Eastern Samar, central Philippines - Switzer, Adam D. (2020)
Typhoon Haiyan crossed the central Philippines on 8 November 2013 and generated storm surge up to 7 m with runup reaching 12 m which deposited overwash sediments inland in many different locations and environments. Collectively, these overwash sediments serve as key modern analogs to compare with geological records of storm events in the region. To date, comparatively few studies have been conducted on sandy storm deposits in carbonate coasts with none to date on storm sediments in coastal caves. Here, we report the grain size and microfossil assemblages of the Typhoon Haiyan overwash sediments from a coastal cave and carbonate beach system in Eastern Samar, central Philippines and infer the source of the Haiyan overwash sediments. We show that overwash sediments inside and immediately outside the cave (beach system) are similar but they can be discriminated from the underlying pre-Haiyan soil through field evidence, grain size, organic matter, and microfossil content. To investigate the source of both the cave and non-cave overwash sediments and in the absence of pre-storm beach sediment samples, we collected post-Haiyan beach sediments in February 2018 when the beach has indicated recovery to its pre-storm condition. We assume that these post-Haiyan beach sediments are representative of pre-storm sediments. The underlying pre-Haiyan soil comprises poorly-sorted, coarse to very coarse sands with higher organic matter content, and a lower microfossil concentration. Also, the pre-Haiyan soil contains foraminifera species similar to those identified in the Haiyan overwash sediments, but rarely containing subtidal foraminifera species. In comparison, the Haiyan overwash sediments share similar attributes with the post-Haiyan coastal sediments, consisting of moderately-sorted gravelly sands predominantly carbonate grains with low organic matter content. The Typhoon Haiyan overwash sediments contain foraminifera species dominated by Amphistegina radiata, Baculogypsina sphaerulata, Calcarina gaudichaudii, Calcarina splengeri suggesting an intertidal environment. Although, lower abundances of benthic species Peneroplis planatus and Quinqueloculina parkeri imply contributions from the subtidal environment. Notably, the Haiyan overwash sediments dominantly contain intertidal foraminifera species with abraded tests similar to foraminifera found in the post-Haiyan beach sediments. The similarity of foraminiferal assemblage and taphonomic condition strongly indicates that the overwash sediments found on the coastal cave were most likely sourced from the beach and reef flat. Our results show overwash sediments in coastal caves are indistinct from those in the nearby beach system indicating the potential of coastal caves to harbor well preserved archives of paleo storm deposits.